Rancangan E-Commerce Mochpoint Menerapkan User Centered Design Berbasis Web - Farid Mukti; Orita Dwi Purbiyanti; Sepitri Daruyani (Journal of Information System Research (JOSH), 2022)
E-commerce is one of the strategies of a trading company to increase sales in the current digital era. Online marketing and transactions have become commonplace in the world of buying and selling. Mochpoint is a store that sells clothing that prioritizes the needs of teenagers to adults. Several obstacles were experienced by Mochpoint when they were still using the old or manual system, namely the promotion of goods still using Instagram, transactions that were not automatic resulted in frequent recording errors and on the customer side it was difficult to find out the stock of goods and the absence of long distance sales which made it easier for the company to expand its marketing area. Mochpoint is a store that implements a B2C (Business to customer) business model, but has not yet used a web-based sales system or e-commerce. Through the use of this website's information system, it is hoped that it will be able to increase the need for data and information to potential customers of ochpoint, where potential customers can exchange data and information to transactions about all products available on mochpoint. . The mochpoint store website was created using the PHP programming language and database processing using MySQL with the website address Http://mochpointweb.epizy.com/. The website design process uses a navigation structure and UML design. The results of the implementation and testing of this website can run well according to the design based on the test results, namely by testing the website on the browser and testing using the black box method